Empowering Older Adults in Digital Security: A Community-Based Analysis of the Tular Nalar Program in Aceh, Indonesia - Nisak, Cut Lusi Chairun; Nisa, Uswatun; Fatia, Dara; Rizkina, Fitriana Dina (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
The escalating incidence of cybercrime in Indonesia has rendered older adults (lansia) one of the most vulnerable populations, primarily due to limited digital literacy and a lack of awareness regarding threats such as hoaks, identity theft, and online fraud. This study analyzes strategies for empowering older adults in digital security, focusing on the implementation of the Tular Nalar program by Mafindo in Aceh Besar District. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using Laverack’s community empowerment framework. The findings indicate that the program fostered active participation, expanded access to information, and strengthened social ties among participants. Facilitators played a crucial role in contextualizing digital security risks based on the lived experiences and local values of the lansia. However, the empowerment process has not yet resulted in collective autonomy, as participants remain reliant on facilitators and have not formed self-sustaining community structures. Disparities in digital literacy, expectations of incentives, and structural barriers further constrain the realization of community-driven empowerment. These results highlight that digital empowerment for older adults is not merely about increasing literacy, but is a complex social process rooted in local structures, cultural values, and community power dynamics. The application of Laverack’s model in this context underscores the need to integrate cultural values and locally grounded approaches into the design of sustainable empowerment strategies for older adults, while also addressing the persistent challenge of achieving community autonomy.